2014
DOI: 10.1021/nl5024468
|View full text |Cite
|
Sign up to set email alerts
|

Density and Energy Distribution of Interface States in the Grain Boundaries of Polysilicon Nanowire

Abstract: Wafer-scale fabrication of semiconductor nanowire devices is readily facilitated by lithography-based top-down fabrication of polysilicon nanowire (P-SiNW) arrays. However, free carrier trapping at the grain boundaries of polycrystalline materials drastically changes their properties. We present here transport measurements of P-SiNW array devices coupled with Kelvin probe force microscopy at different applied biases. By fitting the measured P-SiNW surface potential using electrostatic simulations, we extract t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Previous works for bulk P-Si reported a 'U'-shape energy distribution of GBIS within the band gap, with di↵erent peak densities ranging from 4 ⇥ 10 13 to 10 14 cm 2 eV 1 . [20,21] A recently published paper by Amit et al, [14] showed that this is the case in nanostructures as well. The acceptor and donor interface states were found to have a 'U'-shape distribution as described by the following expressions:…”
Section: Highlymentioning
confidence: 94%
See 2 more Smart Citations
“…Previous works for bulk P-Si reported a 'U'-shape energy distribution of GBIS within the band gap, with di↵erent peak densities ranging from 4 ⇥ 10 13 to 10 14 cm 2 eV 1 . [20,21] A recently published paper by Amit et al, [14] showed that this is the case in nanostructures as well. The acceptor and donor interface states were found to have a 'U'-shape distribution as described by the following expressions:…”
Section: Highlymentioning
confidence: 94%
“…Recently, a low cost, top-down approach of poly-crystalline silicon nanowires (P-SiNWs) synthesis was demonstrated, using a classical fabrication method commonly used in microelectronic industry -the socalled sidewall spacer technique. [11,12,13,14] This top-down approach was previously demonstrated as a good method for biosensor fabrication for several analytes, all in which, a detection limit of femto-molar (fM) level was observed. [15,1,16,17] The main di↵erence between single crystalline silicon (SC-Si) and poly crystalline silicon (PC-Si) is charge trapping at Grain Boundaries (GBs) in the latter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have exploited numerical simulations to investigate the effect of grain boundaries on variability in nanowires [340][341][342][343][344][345] and 3D NAND devices [346,347]. However, several important features of such models still have to be assessed, such as the grain size [348,349], the density and energy distribution of grain boundary traps [350,351], and the mobility degradation and conduction process at the grain boundaries [352,353]. …”
Section: Polysilicon Grainsmentioning
confidence: 99%
“…These high cost fabrication methods are not compatible with mass production. However, polycrystalline silicon SiNWs (poly-SiNWs) synthesis using sidewall spacer top down method [19][20][21] seems to be a lower cost alternative, fully compatible with planar complementary metal oxide semiconductor (CMOS) silicon technology.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%